Identification of novel biomarkers of heavy ion exposure: Proteins, miRNAs and tRNA-derived fragments in serum. (September 2021) - Bai, Hao; Zhang, Tongshan; Wang, Jufang; Hua, Junrui; Wei, Wenjun
Abstract: Space radiation is a major concern for human spaceflight. Especially, the heavy ions in cosmic rays can result in more serious DNA damage and uncertain consequences in carcinogenesis comparing with conventional radiation such as X- or γ-rays. Minimally invasive biomarkers that can be easily and quickly detected at an early stage are valuable for risk assessment of astronauts' space radiation exposure. Serum molecules originating from tissues and blood cells have been emerging as ideal biomarkers. However, the molecules that respond to low dose of heavy ion radiation have not been reported. Here, mice were total-body exposed to different doses of carbon ions with linear energy transfer (LET) of 30 keV/μm. Mouse Antibody Array and RNA sequencing were performed to detect expression profiles of serum proteins and small non-coding RNAs (sncRNAs) at 24 h post-irradiation. After conditional screening and further validation, the expression of 2 proteins, 3 miRNAs and 2 tRNA-derived fragments showed obvious increase or decrease with increasing dose, even in the mice that received as low as 0.1 Gy or 0.5 Gy of carbon ion radiation. In this study, we identified some new proteins, miRNAs and tRNA-derived fragments in serum showing great potential as early biomarkers of exposure to energetic heavy ions. These results might be useful to dose reconstruction and risk assessment of heavy ion exposure in deep space exploration. Highlights: Simple and effective biomarkers of heavy ion exposure during in space missions are urgently needed. New proteins, miRNAs and tRNA fragments in mouse serum were identified responding to carbon ions. The blood molecules-based methods for radiation risk assessment could be expected in future space mission.